Functional Materials - Sahu, Dipti (IntechOpen, 2019)
Functional materials are important materials for any technological needs and the forefront of materials research. Development of functional materials and their effective applications in the frontier fields of cross-multidisciplinary research programs is unique. This book presents an overview of different types of functional materials, including synthesis, characterization and application, and up-to-date treatment of functional materials, which are needed for structural, magnetic, polymeric, electromagnetic, etc. applications. New topics based on polymeric materials and spintronic materials are given for possible applications. The chapters of the book provide a key understanding of functional materials. It is suitable for undergraduates, graduates, and professionals, including engineers, scientists, researchers, technicians, and technology managers.